Situation Report: Hungary, 22 April 1983 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Party Makes No Major Changes in Present Economic Reform / by Alfred Reisch The Thorny Path of "Democratic Progress" / by Judith Pataki The Gypsy Problem Continues to Confront Society / by Eva Lengyel Culture / by Gabor Hajnal Harassment of Dissidents Continue / by Judith Pataki "Beszelo" Describes Censorship and Reviews Biography of Kadar / by Judith Pataki Did Hungary Really Have a Hard Currency Trade Surplus in 1982? / by Cam Hudson Gyula Illyes Dies?